2011
DOI: 10.3390/ijms12042664
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Safflower (Carthamus tinctorious L.) for Seed Quality-Related Traits and Inter-Simple Sequence Repeat (ISSR) Markers

Abstract: Safflower (Carthamus tinctorious L.) is an oilseed crop that is valued as a source of high quality vegetable oil. The genetic diversity of 16 safflower genotypes originated from different geographical regions of Iran and some with exotic origin were evaluated. Eight different seed quality-related traits including fatty acid composition of seed oil (stearic acid, palmitic acid, oleic acid and linoleic acid), the contents of, oil, protein, fiber and ash in its seeds, as well as 20 inter-simple sequence repeat (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 25 publications
8
34
1
2
Order By: Relevance
“…Similar results were obtained in the study by Arzani and Rezaei (2011). Similarities in genotypes grouped in the same cluster could also appear because of participating a common lineage, convergent evolution and selection of superior genotypes by farmers.…”
Section: Resultssupporting
confidence: 85%
“…Similar results were obtained in the study by Arzani and Rezaei (2011). Similarities in genotypes grouped in the same cluster could also appear because of participating a common lineage, convergent evolution and selection of superior genotypes by farmers.…”
Section: Resultssupporting
confidence: 85%
“…In our research, the most polymorphic bands was associated to (CA)n, (AC)n, and (AG)n primers. This is in agreement with the findings of a previous study on safflower having also indicated that (AG)n and (CA)n ISSR primers created the highest polymorphic bands (Golkar et al, 2011). These motifs might have a significant contribution in the safflower genome.…”
Section: Discussionsupporting
confidence: 83%
“…Of 268 fragments produced, 264 polymorphic bands (98.5%) were used to evaluate genetic relationships between the three varieties of L. pumila Benth (alata, pumila, lanceolata) and L. paucifolia (Table 2). The percentage of polymorphism in this study was higher than that reported by previous studies using RAPD (63.4%) (Rafii et al, 2012) and ISSR (0.73%) analysis (Golkar et al, 2011). The number of alleles varied from 5 (I3) to 25 (I2) fragments per primer and ranged from 160 to 2218 bp in size.…”
Section: Resultscontrasting
confidence: 53%